Characterization of extracellular protease-producing bacteria isolated from the coastal environment of Bangladesh and optimization of parameters for enzyme production - Rahman, Md. Habibur; Pranto, Shahittya Mitra; Das, Mousumi; Chakroborty, Koushik; Marma, Mauching; Alam, Md. Shahanoor; Rafiquzzaman, S. M. (Asia-Pacific Journal of Science and Technology, 2025)
Bangladesh’s coastal soil and water harbor a diverse array of native microorganisms that can serve as a significant source of natural protease enzymes, with broad applications in biotechnology, food industries, and environmental sectors. The objective of this study was to isolate and identify native protease-producing bacteria from Cox’s Bazar, a coastal region of Bangladesh, and to optimize the parameters for enzyme production. The bacteria found in the soil and water samples were initially assessed using the zone of inhibition technique and hemolytic test. Five of the isolated bacteria exhibited proteolytic activity and were found to be non-pathogenic. The isolates were subsequently identified through morphological, biochemical, molecular, and evolutionary analysis. Among the identified isolates (Bacillus subtilis, Xenorhabdus nematophilia, and Enterobacter cloacae), B. subtilis was determined to be the most productive bacterial species. A temperature of 35°C, pH 7, 36 h of incubation, and galactose as the carbon source, were the best conditions for protease production. The enzyme activity of B. subtilis was found to be 0.37 U/mL, compared to 0.56 U/mL for a commercial enzyme. These findings suggest that B. subtilis obtained from the coastal water of Bangladesh has the potential to serve as a local source for protease production, with applications in food processing, animal feed, dairy, meat, textiles, waste management, and pharmaceutical industries in Bangladesh. This article has a related Correction